(untitled) (Research, Society and Development, 2020)
Aiming to develop new technologies that directly impact Brazil’s environmental reality in the scope of solid waste management and socio-environmental education, the Synthesis project is developed by the Department of Chemical and Environmental Engineering and by students from the Chemical Engineering course at the Faculty of Technology at the State University of Rio de Janeiro, Brazil. To this end, population of Resende regional campus, where the project is developed, is used as a focus group. Based on the types of waste generated by the campus, alternatives are proposed for their treatment, development of technologies that can be applied to the reality of Brazilian society and measures that encourage society to be part of the waste treatment process, generating a social impact and environmental responsibility. The initial stage of the work developed by the project is the survey of types of waste generated by the campus population in order to determine the priority areas for development of solutions and technological aspects. After this stage, development divisions are determined for each large group of waste on the campus, subsequently aiming at the region’s industrial reality. It has been observed that most of the waste generated was from recyclable materials, followed by non-recyclable materials, as observed in other universities, the biggest divergence has been in the discrepancy of collected compostable material.